A Novel Approach to Propagating Distrust - Borgs, Christian; Chayes, Jennifer; Kalai, Adam Tauman; Malekian, Azarakhsh; Tennenholtz, Moshe (Proceedings of the 6th International Workshop on Internet and Network Economics (WINE), 2010)
Trust propagation is a fundamental topic of study in the theory and practice of ranking and recommendation systems on networks. The Page Rank [9] algorithm ranks web pages by propagating trust throughout a network, and similar algorithms have been designed for recommendation systems. How might one analogously propagate distrust as well? This is a question of practical importance and mathematical intrigue (see, e.g., [2]). However, it has proven challenging to model distrust propagation in a manner which is both logically consistent and psychologically plausible. We propose a novel and simple extension of the Page Rank equations, and argue that it naturally captures most types of distrust that are expressed in such networks. We give an efficient algorithm for implementing the system and prove desirable properties of the system.